2021
DOI: 10.5217/ir.2019.09146
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of biologic therapies for biologic-naïve Japanese patients with moderately to severely active ulcerative colitis: a network meta-analysis

Abstract: remission and spontaneous relapse. 1 Patients with active UC experience significant and clinically meaningful impairment across most aspects of quality of life. 2,3 The prevalence of UC in Japan has been steadily increasing from 18.2 in 1991 and 63.6 in 2005 to 121.9 per 100,000 persons in 2013; 4 about 170,000 patients were receiving treatment for UC in Japan in 2017. 5 Aminosalicylates (5-ASAs) are used as first-line therapy for induction and maintenance of remission in mild to moderately active UC; patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…As there have been few reports about the effectiveness and safety of golimumab in Asian patients, we followed 133 patients with moderate-to-severe UC of about 5 years in 43 teaching hospitals in South Korea to evaluate them in real world. 30 Our study demonstrated the effectiveness of golimumab in Korean patients with moderate-to-severe UC that was consistent with previous studies. 19,25,31,32 After induction dosage regimen of golimumab, more than half of the patients (56%) achieved clinical response at week 6, and more than two-thirds of the patients (67.9%) achieved clinical response at week 22.…”
Section: Discussionsupporting
confidence: 92%
“…As there have been few reports about the effectiveness and safety of golimumab in Asian patients, we followed 133 patients with moderate-to-severe UC of about 5 years in 43 teaching hospitals in South Korea to evaluate them in real world. 30 Our study demonstrated the effectiveness of golimumab in Korean patients with moderate-to-severe UC that was consistent with previous studies. 19,25,31,32 After induction dosage regimen of golimumab, more than half of the patients (56%) achieved clinical response at week 6, and more than two-thirds of the patients (67.9%) achieved clinical response at week 22.…”
Section: Discussionsupporting
confidence: 92%
“…However, anti-TNF therapy increases the risk of infection [ 12 , 13 ]. Tuberculosis (TB) is one infection associated with anti-TNF therapy, which is thought to inhibit the formation of granuloma and thus prevent the suppression of TB activation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…17,26 Our study has highlighted the difference in biomarker dynamics between patients who required and avoided colectomy and demonstrated the potential utility of CAR and CLR early in the treatment course (day 3 post salvage) in predicting infliximab failure. With the expansion of efficacious treatments such as newer biologic therapies and small molecule inhibitors, [27][28][29][30] the ability to predict disease trajectory in ASUC should inform treatment choice-for example, a patient who is likely to require longer term colectomy despite infliximab salvage may warrant more proactive optimization of maintenance therapy with a biologic agent (a top-down approach), while patients with a lower risk of colectomy may only require conventional therapy. [31][32][33] Although the ability to continue biologic therapy in all patients may appear attractive, a careful risk-benefit assessment should be made given such a strategy introduces an additional risk of infections and may not be cost-effective.…”
Section: Discussionmentioning
confidence: 99%